(untitled) (Medical Forum Monthly, 2021)
Objective: To note what a woman has decided in their next pregnancy after having a Cesarean procedure would be based on. Study Design: Observational study Place and Duration of Study: This study was conducted at the department of Obstetrics & Gynaecology, Liaquat University of Medical & Health Sciences Jamshoro's between January and June 2016. Materials and Methods: Data was obtained from admitted patients in the postoperative ward after a caesarean section, as well as outpatient department patients who came for follow-up after a primary caesarean birth. Women were given a pre-designed questionnaire to assess their familiarity with C/S and their expectations for delivery mode in subsequent pregnancies. Results: The study enlisted the participation of 180 qualified women. Their ages ranged from 20 to 40 years, with a mean age of 28.71 SD+5.3 years. The majority of women, 72 percent, were between the ages of 26 and 30, while 34 percent were between the ages of 20 and 25. In terms of indications, foetal distress was observed in 38 =8.5 percent of cases and CPD in 31=7 percent of cases, and these were discovered to be the most common indications of the last C/S. Overall, 22=5.0% of women had hypertension, with PIH accounting for 11=2.5%, preeclampsia accounting for 8 =1.8%, and eclampsia accounting for 3 =0.7%. Breech presentation was observed in 14 =3.1%. When asked about their C/S experience, 71=39.4 percent of women liked and preferred C/S as a mode of delivery in their next pregnancy, Sixty percent of the women (109 women) disliked C/S as a mode of delivery, citing long hospital stays as the reason. C/S is considered expensive by 38 women. 8.6 percent, normal vaginal delivery is natural for 20 women (4.5 percent), 21women (4.7 percent), postoperative pain, dependency on others, inability to do heavy work after C/S in 19 =4.2 percent. Conclusion: Traditional preference of women for the mode of delivery has been vaginal for centuries. Somehow we can also conclude from the study that the preference is still the highest for vaginal delivery.